1993
DOI: 10.1021/jo00056a001
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the enantioselectivity observed in oxazaborolidine-catalyzed reductions of ketones

Abstract: An investigation into the origins of the enantioselectivity observed in oxazaborolidine-catalyzed reductions of ketones was carried out by examination of the reaction surfaces generated using the MNDO Hamiltonian.The reports describing the enantioselective reduction of ketones using stoichiometric borane in the presence of catalytic amounts of chiral oxazaborolidines represent a significant advance in rational reagent design (Figure l).l These reactions presumably occur by the following sequence: (a) complexat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 0 publications
1
30
2
2
Order By: Relevance
“…When a hydride transfers from the BH 3 moiety toward the carbonyl carbon of aromatic ketone, the transition state determined by 3-1d must have a twisted chair structure, which is just the result given by Jones et al [13]. However, it is seen from Tables II and III that among the four structures of the CTO-borane-ketone adducts, the C=O and B BH3 -H BH3 bonds for 3-1a are the longest and their overlap populations are the smallest, whereas the C C=O -H BH3 distance between the carbonyl carbon and the hydride of the BH 3 moiety (2.782 Å) is the shortest.…”
Section: Coordination Of Borane To the Nitrogen Sitementioning
confidence: 62%
See 1 more Smart Citation
“…When a hydride transfers from the BH 3 moiety toward the carbonyl carbon of aromatic ketone, the transition state determined by 3-1d must have a twisted chair structure, which is just the result given by Jones et al [13]. However, it is seen from Tables II and III that among the four structures of the CTO-borane-ketone adducts, the C=O and B BH3 -H BH3 bonds for 3-1a are the longest and their overlap populations are the smallest, whereas the C C=O -H BH3 distance between the carbonyl carbon and the hydride of the BH 3 moiety (2.782 Å) is the shortest.…”
Section: Coordination Of Borane To the Nitrogen Sitementioning
confidence: 62%
“…In other words, when the bonds in the CTO-borane-ketone adducts are changed, the hydride of the BH 3 moiety transfers gradually toward the the carbonyl carbon of aromatic ketone and thus a plausible transition state as illustrated in Figure 2 is formed. For the CBS catalytic system, the results of studies on plausible transition states of the hydride transfer were reported by Jones et al [13], who employed the modified neglect of differential overlap method. Jones et al proposed that the hydride transfer occurs via a chair transition state, whereas Nevalainen, who investigated the CBS-borane-ketone adducts using the ab initio method at the HF/6-31g level (small models were used in computations), conjectured the plausible transition state to stay in a conformation which could be described as a twisted boat [6,7].…”
Section: Coordination Of Borane To the Nitrogen Sitementioning
confidence: 99%
“…Calculations were performed at the level of semiempirical quantum chemistry by the MNDO method 10 included in the Hyperchem package 11. The reactants, the products, the assumed transition states 3, 12 as well as the assumed intermediate structures were optimized without any constraints. Energy (more precisely, enthalpies of formation) values were compared to each other and predictions were confronted with experimental results.…”
Section: Methods Of Evaluationmentioning
confidence: 99%
“…Das stereochemische Ergebnis der durch CBS-Katalysatoren gesteuerten Reduktion von Acetophenon ( [34] sowie neuere DFT-Rechnungen mit dem B3LYP-Funktional [35] liefern eine Erklärung für die Bedeutung des geminalen Diaryl-Substitutionsmusters, bestätigen das Übergangszu-standsmodell 17 und sagen die Annäherung von der Si-Seite als günstigste Topizität voraus. So stimmen berechnete und experimentelle Enantioselektivität zugunsten des (R)-1-Phenylethanols gut überein.…”
Section: Nrunclassified